Research on Application of Multi-Channel Selector in Centrifugal Model Test of Anchoring Slope by Frame Beam - Zhang, Junhui; Li, Feng; Zhang, Shiping; Zhou, Jiankun; Wu, Houming (Frontiers in Earth Science, 2021)
An anchoring frame beam is a very common form of support for reinforced slopes, especially in alpine regions. Centrifugal tests have proved to be an intuitive and effective means of investigating the mechanism of action of frame beams. However, the data acquisition system of the geotechnical centrifuge in service has the problem of a small number of acquisition channels. A multi-channel selector based on the existing acquisition system was proposed, designed, processed, and manufactured, and it was debugged, tested, and applied in a no-load centrifugal test, static pressure model test, and centrifugal model test. The results show that the acquisition mode of the multi-channel selector connected with a maximum of 288 sensors has been changed from “one-to-one” to “one-to-many”. Its influence on various sensor signals is negligible. The multi-channel selector can work normally, which communicates and feeds back with the remote controller in the 1–120 g no-load centrifugal test. In the static load model test, 162 sensor signals were well collected through it. And only 51 channels were used to effectively obtain the signals of 187 sensors in a 70 g centrifugal model test of an anchoring slope with a frame beam. The multi-channel selector can be successfully applied in different use environments, saving time and reducing the cost of obtaining a single set of data.